2009
DOI: 10.1021/ol900123d
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Substituted Phenols by Cationic Rhodium(I)/BINAP Complex-Catalyzed Decarboxylative [2 + 2 + 2] Cycloaddition

Abstract: A new route to substituted phenols has been developed by cationic rhodium(I)/BINAP complex-catalyzed decarboxylative [2 + 2 + 2] cycloadditions of 1,6- and 1,7-diynes with commercially available vinylene carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…New routes for the rapid preparation of substituted phenols and anilines based on a partially intermolecular [2 + 2 + 2] cycloaddition reaction of 1,6‐ and 1,7‐diynes as key‐step have been explored respectively by Tanaka's [51] and Louie's [52] groups under rhodium catalysis. According to their strategies, unstable hydroxyacetylene and free ynamine can be easily replaced by equivalent forms consisting in vinylene carbonate and 2‐oxazolone.…”
Section: [2+2+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…New routes for the rapid preparation of substituted phenols and anilines based on a partially intermolecular [2 + 2 + 2] cycloaddition reaction of 1,6‐ and 1,7‐diynes as key‐step have been explored respectively by Tanaka's [51] and Louie's [52] groups under rhodium catalysis. According to their strategies, unstable hydroxyacetylene and free ynamine can be easily replaced by equivalent forms consisting in vinylene carbonate and 2‐oxazolone.…”
Section: [2+2+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…In this way, benzene rings were prepared avoiding selectivity problems. Several groups have reported the use of enol ethers, vinylene carbonates, or 2‐oxazolones as an alkyne equivalents that undergo dehydration after the cyclotrimerization giving the aromatic final product. If the enol ether component is replaced by vinylene carbonate, a phenol is obtained, whereas the reaction with 2‐oxazolones gives anilines.…”
Section: Rhodium and Iridium Catalysismentioning
confidence: 99%
“…Tanaka and co-workers also reported a similar methodology utilizing a different leaving group. 42 Zhang and Louie extended this approach to the synthesis of anilines 71 using 2-oxazolone (70), which can be used as an alternative for ynamides (Scheme 27). 43 They also demonstrated that the reaction proceeds with full regioselectivity when two different R groups are used (e.g., H, Me).…”
Section: Other [2+2+2] Approachesmentioning
confidence: 99%